If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -68 = 179 Reorder the terms: -68 + 13x = 179 Solving -68 + 13x = 179 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '68' to each side of the equation. -68 + 68 + 13x = 179 + 68 Combine like terms: -68 + 68 = 0 0 + 13x = 179 + 68 13x = 179 + 68 Combine like terms: 179 + 68 = 247 13x = 247 Divide each side by '13'. x = 19 Simplifying x = 19
| 12/4x=16x/4 | | X^2+y^2-2ax=0 | | rad(3x+25)=x+7 | | 3x^2-5xy-2y^2= | | 5x+9+6x+3= | | 6/6x=89x/1 | | 3x+5+4x+7=19 | | 6*6x=89x*1 | | -9d+7-6d=-133 | | 2b^2+4b+2=0 | | 3x+2-x=6+5x-3 | | m-1/3=-9 | | 2*5x=5x*6 | | 6x+6+7x+5=115 | | 3*x=7*1x | | 6x+6+8x+7=69 | | -2=-49x(2)-7x | | 4a^2-147=0 | | -2g^2-6g+14x^2/(g+5) | | 4x+4+2x+9=31 | | -2g^2-6g+14x^2/g+5 | | 12x+16=3x+9 | | 28x^5-36x^4+8x^3= | | 7x*6=34x*6 | | 5x+2+2x+3=47 | | X/7+10=9 | | 1/2n+10=20 | | 2x-9=-33-4x | | 34x*6=7x*6 | | 2x+0.625=3x-0.625 | | X/3+5=-1 | | 3x-6=-1 |